Deconstructing Dominus Litis Towards the Parens Patriae Paradigm of the Prosecutor's Office in Protecting Child Victims - Zenericho; Aarce Tehupeiory; Rospita A. Siregar; Mompang L. Panggabean (Law Research Review Quarterly, 2026)
This study aims to reconstruct the role of the Prosecutor's Office in the Indonesian juvenile criminal justice system, particularly in addressing the phenomenon of child delinquency where the perpetrator is under 12 years old. The fundamental problem arises when the prosecution process is formally halted (based on Article 21 of the SPPA Law), which implicitly causes the Prosecutor to ignore the victim's rights by his capacity as Dominus Litis. Through normative juridical research methods with a philosophical and conceptual approach, this study identifies a systemic failure in realizing substantive justice for child victims. The originality of this thinking lies in the deconstruction of the Prosecutor's rigid role from merely a public prosecutor to a representative of the state through the doctrine of Parens Patriae. The results of the study recommend an integrative protection model based on Pancasila Justice, where the Prosecutor acts as a restorative catalyst that guarantees restitutio in integrum for child victims through an institutionalized non-litigation mechanism.